Emigrant wobec polskości. Literackie prowokacje Mariana Pankowskiego - Pasterska, Jolanta (Tematy i Konteksty, 2011)
The basic idea of writings by Marian Pankowski refers to the attitude of rebellious artist: independent author deeply convinced of his own value, writer constantly on search for his most suitable literary form. Literary provocations by Pankowski are treated as the expression of discontent to stereotypical images not only of such concepts as homeland and exile, but also religion and Western civilization. Polemic with history, Romanticism and religion, as well as unrestrained eroticism, are all perceived as an attempt to free the artistic individuality limited by obsolete forms and masks. Demythologization of Polish emigration – through exposing Pankowski’s compatriots who imitate the tradition of romantic post-insurrection émigrés – serves the same purpose. True Polishness is associated by Pankowski with the pattern remembered from his childhood: simplicity unaffected by politics, ideology, artificial pathos and hypocrisy. Opposition to this pattern is described in the images of Polishness abroad, associated with religious and political trashy meetings that commonly made use of symbols such as Black Madonna of Częstochowa and the Great Emigration. Pankowski accepts the role of an outsider alienated from the groups of both artists in Poland and émigrés in order to provoke Poles to discuss the subject matter of Polishness itself. However, in his struggle against any examples of hypocrisy Pankowski does not expose the very source of his rebellion and from his extraordinarily vivid and carefully adjusted literary descriptions one cannot draw any moral. As a result, his experimental writings exceed and violate all the boundaries (political, literary, genre, moral) and thus cannot be undisputedly classified. His works have as many enthusiasts as they have adversaries. Undoubtedly, his art meets the basic requirement of aesthetics and does not leave its reader indifferent and unmoved.